The silent constitution of territory. (9th November 2018) - Doyle, Oran
Abstract: Legal systems and states typically, and perhaps necessarily, have a limited geographical scope Territorial issues infrequently become the focus of constitutional scrutiny, and then usually in the peripheral instances of contested territorial claims and secession. Drawing on a newly compiled dataset of all state constitutional provisions addressing territory, I develop a new theory about the general relationship between laws and the geographic limits on their application. In particular, I advance an explanation both for why most constitutions do not seek to define the national territory with any specificity and for why some constitutions attempt that task. I argue that the silent conventions of geographically discrete groups determine the geographical scope of a constitution's application. Constitutional delineations of the national territory are therefore unnecessary. Nevertheless, textual delineations of territory can achieve three purposes: they can clarify the silent conventions, express territorial claims over contested territory, and contract the scope of the constitutional order. This relationship between silent conventions and constitutional text has implications for the question of whether constitutions should include a right to secede and for how constitutions can function as sites of territorial contestation.